Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am given the piecewise function $G(t)$, which is written below, and I am asked to find all values of the parameters $\alpha$ and $\beta$ for which the function $G$ is differentiable at $t=1$.

$G(t)=\alpha t^{2}+\ln(t)$ if $t\geq 1$

$G(t)=\beta e^{t-1}-2t$ if $t<1$

I am also given the hint:

You may assume that:$$\lim_{x\to0} \frac{e^{x}-1}{x}=1$$ $$\lim_{x\to 0} \frac{\ln(1+x)}{x}=1$$

I know that the function must be continuous, so $\lim\limits_{t\to 1^+}G(t)=\lim\limits_{t\to 1^-}G(t)$. This leaves me with $\beta-2=\alpha$. I am a bit confused with my next steps. I believe I must use the definition of a derivative in order to set the slopes of each parts of $G(t)$ to be equal to each other. We are not far enough in the course to simply take the derivatives of each part of $G(t)$.

share|cite|improve this question
up vote 2 down vote accepted

For the function to be differentiable at $1$, you need $$\lim_{x\to 0}\frac{G(1+x)-G(1)}{x}$$ to exist. Note that $G(1) = \alpha$.

Evaluating the limit from the right, we have $$\begin{align*} \lim_{x\to 0^+}\frac{G(1+x)-G(1)}{x} &= \lim_{x\to 0^+}\frac{\alpha(1+x)^2+\ln(1+x)-\alpha }{x}\\ &= \lim_{x\to 0^+}\frac{\alpha\bigl((1-x)^2-1\bigr) + \ln(1+x)}{x}\\ &= \lim_{x\to 0^+}\frac{\alpha(x^2-2x)}{x} + \lim_{x\to 0^+}\frac{\ln(1+x)}{x}\\ &=\lim_{x\to 0+}\alpha(x-2) + 1\\ &= 1-2\alpha. \end{align*}$$

Now try evaluating the limit from the left in a similar manner; the two limits must be equal for the derivative to exist. (If the derivative exists, this automatically guarantees continuity).

share|cite|improve this answer
It worked out very well, thank you! – Malthus Oct 20 '11 at 14:56

Your belief is true, the definition of the derivative is in order here:

$ G'(t) = \lim_{h\rightarrow 0}\frac{G(t+h)-G(t)}{h} $

And in your case, $t=1$, so you need to evaluate $G(1)$ and $G(1+h)$ for the right-end limit and $G(1-h)$ for the left-end limit of $G'(t)$ (just as you did for the continuity part). When you evaluate

$ \lim_{h\rightarrow 0}\frac{G(t+h)-G(t)}{h} $

you'll see that the two fractions given in the "you may assume" part will pop up and you can use those assumptions to help you with the limit.

I can clarify more if needed.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.